До питання виникнення дефектів поверхні сталевої штаби при валковій розливці - Ноговіцин, О.В.; Нурадінов, І.А.; Петренко, Д.О. (Physico-technological Institute of Metals and Alloys, 2023)
The article is devoted to identify the causes and mechanism of the formation of surface defects on steel strips obtained by the method of roll casting. Several well-known hypotheses are given that explain the causes and mechanism of the formation of defects such as cracks, wrinkles, bumps, "crocodile skin", etc. The mechanism of the appearance of surface defects based on a theoretical analysis of the flow parameters and stresses of the hardened metal in the rolling zone, the title "rolling effect", are discussed in the article. Metal in the rolling zone, as a result of plastic deformation, is forced to move relative to the surface of the roll both forward and backward. A backward movement of the metal from the deformation zone, acting on the metal crust in the crystallization zone, leads to its compression in the tangential direction and delamination in the radial direction, that is, preconditions are created for the destruction of the metal crust before entering the deformation zone. Under the influence of these stresses, the crust of the hardened metal can peel off and/or break off from the surface of the roll. The situation is aggravated by the fact that for carbon and low alloy steels, the transition from the viscous to the brittle state occurs at temperatures close to the “solidus”. The cavities formed between the roll and the solid metal are filled with liquid melt, forming a mixture of fragments of a hard crust and a liquid or semi-liquid melt. In the advance zone, the outer layers of the strip under the action of tensile stresses are deformed and can take the form, for example, of a “crocodile skin”. To prove the proposed hypothesis, calculations were carried out to evaluate the influence of the parameters of roll casting technology (TRC) on the kinematic and force parameters in the rolling zone. This allowed us to obtain a number of important practical conclusions. When casting a steel strip on TRC, it is advisable to reduce the reduction to a minimum that will only ensure welding of hardened crusts, that is, through crystallization of the strip should be completed in close proximity to the metal exit line from the rolls. The implementation of this technology will allow the casting process to be carried out at high speed with a low pressure force on the rolls. It is advisable to transfer the formation of the required quality of the cast strip to subsequent hot and cold rolling.